A demonstration of compilability for UML template instances - Farinha, J. (2021)
Because of the thin set of well-formedness rules associated to Templates in UML, ill-formed elements may result from bindings to templates. Although such ill-formedness is generally detected by some UML validation rule, the problem is poorly reported because it is not normally imputed to the binding. Typically, such problems are detected as non-compilable code in the template instances. A set of well-formedness rules, additional to those of the standard UML, was proposed as a way to ensure the compilability of instances and prevent this problem from occurring. Such set of constraints was proposed in a previous paper and named Functional Conformance, but a demonstration of its effectiveness was not yet provided. Such a demonstration is outlined in the current paper. Carrying out the demonstration revealed the need for two more rules than those previously envisioned for Functional Conformance.